Advanced Research Techniques: Theories, Methods, and Practices (Volume-2) - R. Sundar,; N. Maliqjan, (AG Volumes, 2025)
Advanced Research Techniques: Theories, Methods, and Practices is a comprehensive and insightful guide that bridges the gap between foundational research knowledge and contemporary research innovations. This book is tailored for students, academics, and professionals across disciplines who seek to elevate their understanding of research methodologies in an ever-evolving academic and technological landscape.The book covers a wide range of topics, from traditional research theories and frameworks to advanced methods, including big data analytics, artificial intelligence in research, computer-assisted qualitative analysis, and mixed-methods design. Each chapter is designed to offer a clear conceptual foundation, followed by practical applications and real-world examples, enabling readers to implement these techniques effectively in their own work.Emphasis is placed on ethical research practices, data transparency, and methodological rigor. The book also addresses the growing importance of interdisciplinary research and equips readers with tools to navigate complex research questions using both qualitative and quantitative approaches.Advanced Research Techniques is more than just a textbook—it is a strategic resource for developing the critical thinking, technical skills, and ethical awareness necessary for conducting high-impact research. Whether used as a course companion or a reference guide, this book empowers readers to explore, question, and innovate in their research endeavors.